2018
DOI: 10.1590/s1980-220x2017039903364
|View full text |Cite
|
Sign up to set email alerts
|

Programas de Controle de Infecção Hospitalar: avaliação de indicadores de estrutura e processo

Abstract: Among the four instruments applied to assess hospital infection control programs, only two presented results with more than 80.0% of conformity: those related to the epidemiological surveillance and technical-operational structure assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
28

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 13 publications
3
23
0
28
Order By: Relevance
“…It is estimated that, in developing countries, every 100 hospitalized patients will be affected by IH, causing ethical, legal and social problems, as well as increased costs related to hospitalization, lengthening hospitalization time, and in more severe cases leading to deaths. 3 Staphylococcus, especially S. aureus and S. epidermidis, are among the most important microorganisms associated with nosocomial infections. These infections constitute an important problem in hospitals, and intensive care units (ICUs) have the highest incidence of this type of infection.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that, in developing countries, every 100 hospitalized patients will be affected by IH, causing ethical, legal and social problems, as well as increased costs related to hospitalization, lengthening hospitalization time, and in more severe cases leading to deaths. 3 Staphylococcus, especially S. aureus and S. epidermidis, are among the most important microorganisms associated with nosocomial infections. These infections constitute an important problem in hospitals, and intensive care units (ICUs) have the highest incidence of this type of infection.…”
Section: Introductionmentioning
confidence: 99%
“…A IH é uma condição infecciosa que pacientes hospitalizados estão expostos, devido ao seu tempo de internação e aos procedimentos aos quais o mesmo é submetido. O prolongamento do tempo de internação é um agravante a esses pacientes, principalmente aos internados nas UTI`s, visto que, estimativas afirmam que ao menos 5% dos pacientes internados em hospitais adquirem uma infecção 1,10 .…”
Section: Discussionunclassified
“…A Infecção Hospitalar (IH) é um a complicação muito recorrente e que afeta milhares de pessoas em todo o mundo. Devido a isso, as consequências ocasionadas tratam-se tanto de problemas éticos, jurídicos e sociais, quanto de custos relacionados ao prolongamento do tratamento e ao tempo de internação, bem como, ao tempo de exposição do paciente a infecções e patógenos, o que em casos mais graves, pode levar ao aumento no número de óbitos 1 .…”
Section: Introductionunclassified
“…Microbial transmission is often observed when good practices in health are violated (3) , which justifies the association of lack of adherence to the recommended precautions, especially low adherence to hand hygiene, with the occurrence of HAIs. Health professionals' hands are pointed as one of the main microbial transmission routes (4) .…”
Section: Introductionmentioning
confidence: 99%
“…One of the main challenges to control the risk of infection implies to invest in changing the behavior of health professionals (3) , given that previous studies have shown that promoting hand hygiene requires a multimodal approach that includes personal, cultural, and institutional factors (6,(10)(11) . These findings have suggested that behavioral determinants such as attitude, social influence, and self-efficacy can play a crucial role in adherence to hand hygiene practices (12) .…”
Section: Introductionmentioning
confidence: 99%